Ekonomi Lokal di Era Digital: Analisis Data Usaha Berbasis Platform Digital di Kota Mataram - Bulan Aprilia; Emmalia Zachwa; Ranang Hamdani; Selviana Ayu; Syakira Hulwah Firmayanti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of a digital platform-based economy has driven the transformation of micro, small, and medium enterprises (MSMEs) in urban areas, including Mataram City. This study aims to analyze the characteristics of digital platform-based businesses based on their type, regional distribution, and platforms used, as well as assess the potential and constraints of utilizing digital platform data as a source of local economic statistics. This study uses a descriptive qualitative approach with secondary data collection techniques through online observations on five digital platforms: GrabFood, GoFood, Instagram, TikTok, and Facebook during March 2026. Data obtained from 445 business units were then classified based on business category, sub-district location, and platform type. Data analysis was conducted using content analysis techniques and simple descriptive statistical analysis to identify distribution patterns and trends in digital platform usage. The results show that the culinary sector dominates at 96.6 percent, with the highest concentration in Mataram and Cakranegara Districts. GrabFood is the most dominant platform compared to other platforms. The research findings indicate that digital platform data has the potential to be a source of actual and real-time local economic information, but still faces obstacles in accessibility, data standards, and digital literacy. This study recommends integrating digital platform data with official statistics to strengthen the accuracy of local economic analysis